Effects of Guanidinoacetic Acid on Lean Growth and Methionine Flux in Cattle - M. Ardalan; M. D. Miesner; C. D. Reinhardt; D. U. Thomson; C. K. Armendariz; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:To evaluate the effect of supplementing guanidinoacetic acid in the presence or absence of L-methionine on nitrogen retention (lean tissue growth) when cattle were purposefully maintained under conditions of a methionine deficiency. Study Description:Seven ruminally-cannulated Holstein steers (355 lb) were used in an experiment where each steer received each of six treatments. Treatments were abomasal infusion of 0 or 6 g/day methionine, and 0, 7.5, or 15 g/day guanidinoacetic acid, with all combinations represented. Energy was supplied by ruminal infusion of volatile fatty acids and abomasal infusion of glucose. All essential amino acids except methionine were infused abomasally to make methionine the most limiting amino acid. The BottomLine:Supplementation with 15 g/day of guanidinoacetic acid tended to increase lean tissue growth when steers received supplemental methionine, probably by increasing creatine synthesis by the steers.
Keywords: guanidinoacetc acid; methionine; nitrogen retention